The analysis of wireless LAN performance between Direct Sequence Spread Spectrum (DSSS) and Frequency Hopping Spread Spectrum (FSSS) / Hairul Bariyah Ab Samad - Ab Samad, Hairul Bariyah (2007)
This paper deals with the concept and the application of Wireless LAN technology. The purpose of this project is to evaluate the concept and the application of the Wireless LAN technology focus on the type of frequency. The analysis of the project is based on the simulation model of Wireless LAN network using OPNET MODELER 8.1 software. The model was designed to analyze the performance of Direct Sequence Spread Spectrum (DSSS) and Frequency Hopping Spread (FSSS). The scenario consists of a wireless and a wire line network. The site_l of subnetO and subnetl and site_2 of subnetO and subnet_l each contain 5, 10, 15 or 20 wireless stations; all stations comply with the wireless LAN (802.11) protocol. The Access Point nodes in site_l and site_2 of subnet_0 connect to the server's .The Access Point nodes in site_l and site_2 of subnet_l are to communicate with servers at the remote site via IP cloud. The results for the model network were performed in the graph which has been generating by the software itself. The performance issues of the Wireless LAN were covered for throughput of the Wireless LAN. All the results were obtained to show the performance issues for DSSS and FSSS.